Kinematics of KO sprint cross country ski racing - Zory, R.; Barberis, M.; Schena, F.; Rouard, A. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction The diagonal stride of the classical technique in cross-country skiing has been used in distance races from 5 Km to 50 Km. Numerous studies on kinematics indicated that cycle velocity (CV) was related to cycle length (CL) and not to cycle rate (CR) (Bilodeau et al, 1996). These results were similar whatever gender and terrain conditions. In recent years, a new short race (KO sprint) appeared in the panel of competitions of the cross country skiing. The short distance (less than 2km) represented very intensive efforts. In regard to the importance of CV, CL and CR in long distance races, the aim of our study was to analysed these parameters during this short race in elite skiers. Methods 55 senior males cross-country skiers participated in a 1.2-Km classic race of the 2004 world cup. Skiers were filmed in the sagittal plane using a digital camera (Panasonic NV-GX7 EG, PAL., 25 frames / s) fixed on a tripod 7.30 meters perpendicularly from the ski tracks. The video recording area was situated at the end of the last uphill (5°) portion of the race. It was chosen in reference to previous work showing that a slightly uphill terrain is able to discriminate subjects of different performance abilities. Video images were digitised frame by frame for all the body joints and for skis and poles. All kinematics coordinates were smoothed using a Butterworth Low-Pass filter. CV, CL and CR was calculated from the CG trajectory. Results Cycle parameters in short KO sprint race were characterised by higher CV (Present study: 4.77m.s-1; Bilodeau et al. 1996: 3.4-3.9 m.s-1; Marino et al. 1979: 3.78 m.s-1) with similar range of CL and higher CR in regard to previous results on long distance races with similar uphill (fig. 1). In addition, opposite to long races, significant correlation was observed between CV and CR (r = 0.65; P=0.000) and not with CL (r=0.19) (fig. 2). Discussion/Conclusion In regard to the longer distance races, KO sprint was characterised by similar CL values with higher CR and CV. This result confirmed previous observations of increase in velocity in other cross country techniques (Hoffman et al. 1995).Contrary to previous studies the decrease of the duration of the cycle did not affect the CL. For Norman et al. (1989) CL was mainly determined by "the leg and pole thrust". Our results suggested that skiers maintained an effective thrust even the increase of CR. In addition, contrary to the long distance races, CV in KO sprint was related to CR and not to CL. The high CR and the great correlations between CR and CV highlighted the determinant part of temporal cycle parameter in velocity production suggesting higher power requirements for this kind of race.